Analysis of Chemical Use in Room Cleaning by Room Attendants at Lion Hotel Manado - Mohd Supriadi; Jongky Wuner Alfius Kamagi; Hendry Moudy Estefanus Kumaat (Jurnal Studi Perhotelan dan Pariwisata, 2026)
Purpose: This study aimed to analyze the use of cleaning chemicals in room cleaning activities performed by Room Attendants, evaluate compliance with Standard Operating Procedures (SOPs), and identify strategies to optimize chemical use at Lion Hotel & Plaza Manado.Research Methodology: A descriptive qualitative approach was used. Data were collected through direct observation, semi-structured interviews with seven Room Attendants and two Housekeeping Supervisors, and documentation of housekeeping SOPs and operational records. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, conclusion drawing, and verification.Results: The findings indicate that chemical use generally follows housekeeping operational procedures, particularly in the selection of cleaning chemicals according to their functions and cleaning areas. However, several deviations from the SOPs were identified, including chemical dilution without standardized measuring tools, inconsistent implementation of recommended contact times, and irregular use of Personal Protective Equipment (PPE). These deviations were primarily influenced by the work habits, operational workload, and limited cleaning time. Conclusion: Chemical use generally met operational requirements; however, SOP implementation requires improvement through standardized dilution practices, regular training, stronger supervision, and consistent PPE use to enhance operational effectiveness and occupational safety.Limitations: This study was conducted in a single hotel using a qualitative approach, which limits the generalizability of the findings.Contribution: This study provides practical recommendations for improving chemical management, strengthening SOP compliance, and promoting occupational safety in hotel housekeeping operations, while enriching the empirical evidence on housekeeping practices in Indonesian hotels.